Micro-CT Assessment of Filling Removal Effectiveness in the Apical Third of Curved Canals with Different Types of Anatomy - Fruchi, lincoln de Campos; Alcalde, Murilo Priori; Amoroso-Silva, Pablo Andres; Vivan, Rodrigo Ricci; Bramante, Clovis Monteiro; Duarte, Marco Antônio Húngaro (Iranian Endodontic Journal, 2024)
Introduction: The aim of this study was to assess the effectiveness of filling removal material from the apical third of curved mesial root canals of mandibular molars. Reciprocating instrumentation followed by additional rotary instrumentation with instruments made of alloys with different heat treatments was evaluated. Materials and Methods: Thirty-six mesial roots of mandibular molars were divided into two groups: Group Class IV consisted of 16 roots with two independent canals, and Group Class II consisted of 20 roots with two canals that merged into one at their apical level. Each of these two groups were further divided into two subgroups, according to the additional rotary instrument used after the reciprocating instrumentation: Group RH and Group RM for Hyflex and Mtwo, respectively. After each procedural step, the roots were scanned by micro-tomography. After each step of filling removal, the Wilcoxon matched pair test and the Mann-Whitney test were used for the evaluation between groups. The significance level adopted was 5%. Results: Significant differences were observed between groups with different Class II and Class IV anatomies, regarding filling removal after Reciproc (P<0.05). After the use of an additional rotary instrumentation, no differences were observed between the two groups (P>0.05). Conclusions: In the apical third of mesial roots of mandibular molars with Class II anatomy, an additional rotary instrumentation was shown to be necessary for improving the removal of filling material after using the single-file reciprocating instrumentation technique.